Performed rhetorical and monetary at the radiator Azadi - new lighting (Journal of the College of Basic Education, 2022)
The most important thing in the biography of the scientific radiator is its teaching by a group of great scholars such as: Abu Hatem al-Sijistani, al-Mazzani and al-Riyashi. It also teaches on its hands and is taught by a number of scholars such as: He was the imam of his time in the language and literature after Sheikh Almazni, and his knowledge has had a great impact on the diversity of his research fields, and has attracted the attention of many researchers and scholars to His grammatical and linguistic efforts, while the coolant has critical opinions Taint in his books; the question that arises here: Was it clear to file cash efforts in the Arab Monetary? Can we prepare him as a critic of the era? Was his criticism confined to linguistic and grammatical aspects without touching the rhetorical and aesthetic faces of literary texts? Its place and the views of its old critics. In this research, we will focus on answering these questions according to an analytical descriptive approach based on the extrapolation of texts and their analysis, explaining the personality of the radiator and its status among contemporary scientists, as well as the presentation of its critical efforts in theory and practice.